Ablating hedgehog signaling in tenocytes during development impairs biomechanics and matrix organization of the adult murine patellar tendon enthesis. Issue 8 (14th April 2015) - Breidenbach, Andrew P.; Aschbacher‐Smith, Lindsey; Lu, Yinhui; Dyment, Nathaniel A.; Liu, Chia‐Feng; Liu, Han; Wylie, Chris; Rao, Marepalli; Shearn, Jason T.; Rowe, David W.; Kadler, Karl E.; Jiang, Rulang; et al.
ABSTRACT Restoring the native structure of the tendon enthesis, where collagen fibers of the midsubstance are integrated within a fibrocartilaginous structure, is problematic following injury. As current surgical methods fail to restore this region adequately, engineers, biologists, and clinicians are working to understand how this structure forms as a prerequisite to improving repair outcomes. We recently reported on the role of Indian hedgehog (Ihh), a novel enthesis marker, in regulating early postnatal enthesis formation. Here, we investigate how inactivating the Hh pathway in tendon cells affects adult (12‐week) murine patellar tendon (PT) enthesis mechanics, fibrocartilage morphology, and collagen fiber organization. We show that ablating Hh signaling resulted in greater than 100% increased failure insertion strain (0.10 v. 0.05 mm/mm, p<0.01) as well as sub‐failure biomechanical deficiencies. Although collagen fiber orientation appears overtly normal in the midsubstance, ablating Hh signaling reduces mineralized fibrocartilage by 32%, leading to less collagen embedded within mineralized tissue. Ablating Hh signaling also caused collagen fibers to coalesce at the insertion, which may explain in part the increased strains. These results indicate that Ihh signaling plays a critical role in the mineralization process of fibrocartilaginous entheses and may be a novel therapeutic to promote tendon‐to‐bone healing. © 2015 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 33:1142–1151, 2015.